Bimbingan Islam Pada Pendidikan Anak Usia Dini - Rofiki Rofiki; Faridatul Jannah; Robiatul Adawiyah (Al Tahdzib: Jurnal Pendidikan Islam Anak Usia Dini, 2022)
The research objective is to describe guidance activities that can be carried out at Early Childhood Education Institutions. The research method is descriptive qualitative through a library study approach. Data collection techniques with documentation studies and data processing with reduction, data presentation and drawing conclusions. The results of the study: the method of religious guidance in early childhood can be carried out individually and in groups through in-class learning. The forms of religious guidance that can be carried out are (1) prayer guidance by teaching prayer movements. (2) speech guidance to train children's speaking courage. (3) prayer guidance to love Rasulullah SAW. (4) Koran guidance to teach hijaiyanh letters and recite the Koran fluently. (5) guidance on the pillars of faith and pillars of Islam so that children can memorize the pillars of faith and Islam.